INTERPRETASI MODEL ANOMALI MAGNETIK BAWAH PERMUKAAN DI AREA PERTAMBANGAN EMAS RAKYAT DESA CIHONJE, KECAMATAN GUMELAR, KABUPATEN BANYUMAS - Sehah, Sehah; Raharjo, Sukmaji Anom; Prasetyo, Chandra Adi (BERKALA FISIKA, 2015)
Measurement of magnetic data has been done in the area of ​​the gold mining in the village of Cihonje, the district of Gumelar, the regent of Banyumas in May to June 2013. Based on the modeling that has been conducted on the local magnetic anomalies along cross section of AB obtained six models of subsurface rock, while for along cross section of AB obtained five models. Based on the modeling results, rock formations that developed in the research area are Tapak formation, Halang formation, andesite-basaltic, and the alternating formation of the sandstones with some other rocks. The magnetic susceptibility of subsurface rock in the research area are interpreted ranged from 0.0039 to 0.0174 cgs units with the average magnetic susceptibility of rocks is estimated equal to 0.0099 cgs units that interpreted as the alternating formation of sandstone and claystone from Halang formation. The mineralization of gold ore is estimated to occur in almost of all subsurface rocks, but the most dominant mineralization is estimated to occur in the Halang formation especially on the alternating formation of sandstone and claystone. The gold ore mineralization occurs in the form of veins of pyrite, chalcopyrite, galena, and the others, that fill the cracks and the pores of the rocks. Keywords: magnetic anomaly, gold mining, Village of Cihonje